2020
DOI: 10.34067/kid.0003792020
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Associated with the Use of Renin-Angiotensin-Aldosterone System Blockade in Hospitalized Patients with SARS-CoV-2 Infection

Abstract: BackgroundData regarding the benefits or harm associated with the continuation of angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin II receptor blockers (ARBs), especially the effect on inflammation, in patients who are hypertensive and hospitalized with coronavirus disease 2019 (COVID-19) in the United States are unclear.MethodsThis is a single-center cohort study of patients sequentially hospitalized with COVID-19 at Stony Brook University Medical Center from March 7, 2020 to April 1, 2020, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(57 citation statements)
references
References 32 publications
0
57
0
Order By: Relevance
“…The comparison of mortality and clinical severity outcomes between ACEI/ARB users and non-ACEI/ARB users with COVID-19 is summarized in Table 2 . There were 50 studies [ 35 – 38 , 41 45 , 48 – 51 , 53 59 , 61 , 62 , 64 – 82 , 85 – 93 ] and 36 studies [ 35 , 36 , 39 41 , 43 – 53 , 55 , 56 , 59 – 63 , 66 , 71 , 74 , 75 , 78 , 80 , 83 85 , 89 – 92 ], respectively, that reported mortality outcomes and clinical severity outcomes among COVID-19 patients with and without the use of ACEIs/ARBs. Among 50 studies that reported mortality outcomes, 24 studies [ 35 , 36 , 54 , 56 , 57 , 59 , 64 , 66 , 67 , 69 , 70 , 72 , 74 – 78 , 80 , 81 , 86 , 88 , 89 , 92 , 93 ] provided adjusted mortality estimates with the use of an ACEI/ARB relative to the non-use of an ACEI/ARB.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The comparison of mortality and clinical severity outcomes between ACEI/ARB users and non-ACEI/ARB users with COVID-19 is summarized in Table 2 . There were 50 studies [ 35 – 38 , 41 45 , 48 – 51 , 53 59 , 61 , 62 , 64 – 82 , 85 – 93 ] and 36 studies [ 35 , 36 , 39 41 , 43 – 53 , 55 , 56 , 59 – 63 , 66 , 71 , 74 , 75 , 78 , 80 , 83 85 , 89 – 92 ], respectively, that reported mortality outcomes and clinical severity outcomes among COVID-19 patients with and without the use of ACEIs/ARBs. Among 50 studies that reported mortality outcomes, 24 studies [ 35 , 36 , 54 , 56 , 57 , 59 , 64 , 66 , 67 , 69 , 70 , 72 , 74 – 78 , 80 , 81 , 86 , 88 , 89 , 92 , 93 ] provided adjusted mortality estimates with the use of an ACEI/ARB relative to the non-use of an ACEI/ARB.…”
Section: Resultsmentioning
confidence: 99%
“… ACEI angiotensin-converting enzyme inhibitor, ARB angiotensin receptor blocker, CI confidence interval, COVID - 19 coronavirus disease 2019, HR hazard ratio, N/A not available, OR odds ratio a The definition of severe/critical disease in the studies by Amaouche et al [ 35 ], Feng et al [ 39 ], Feng et al [ 40 ], Gao et al [ 41 ], Hu et al [ 43 ], Huang et al [ 44 ], Li et al [ 45 ], Li et al [ 46 ], Liu et al [ 47 ], Meng et al [ 48 ], Peng et al [ 49 ], Yan et al [ 52 ], and Yang et al [ 53 ] is based on the definition given in ‘Diagnosis and Treatment Protocol for Novel Coronavirus Pneumonia’ by Chinese National Health Commission; Chen et al [ 36 ] is based on the development of multiple organ dysfunction syndrome; Tan et al [ 50 ] is based on the development of acute respiratory distress syndrome; Xu et al [ 51 ], Fosbøl et al [ 59 ], Dauchet et al [ 60 ], Liabeuf et al [ 61 ], Zhou et al [ 63 ], Felice et al [ 66 ], Sardu et al [ 71 ], Dalan et al [ 74 ], Son et al [ 78 ], López-Otero et al [ 80 ], Argenziano et al [ 83 ], Chaudhri et al [ 85 ], Lam et al [ 89 ], Mehta et al [ 90 ], Richardson et al [ 91 ], and Shah et al [ 92 ] are based on the requirement for admission into intensive care units; Zeng et al [ 55 ] is based on the guideline for community-acquired pneumonia; Zhang et al [ 56 ] is based on the development of septic shock; Oussalah et al [ 62 ] is based on the requirement for intubation or mechanical ventilation; Choi et al [ 75 ] is based on the requirement for mechanical ventilation, admission into intensive care units, continuous renal replacement therapy, or extracorporeal membrane oxygenation; and Chang et al [ 84 ] is based on the requirement for admission into intensive care units or intubation b Preprint …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations